Children's Culture and Citizenship in Argentina A History of Billiken Magazine (1919-2019) - Rea, Lauren (White Rose University Press, 2023)
Argentina's Billiken was the world's longest-running children's magazine, publishing 5144 issues over one hundred years. It educated and entertained generations of schoolchildren and came to occupy a central role in Argentine cultural life. This volume offers the first academic history of the whole lifespan of Billiken as a print magazine, through to its transition into a digital brand. As an editorial project founded at the time of the massification of print culture, Billiken was in the business of creating future citizens. From its transnational and literary beginnings, Billiken quickly became organised around the school year, offering valuable extra-curricular material aligned to the patriotic drivers of state schooling. Billiken told the story of the Argentine nation, cyclically and repeatedly, gaining such momentum that it became part of the nation's story itself. This volume adopts a multi-disciplinary approach to take account of the many different facets of Billiken's content born from a combination of ideological, commercial, political and cultural drivers. This history of Billiken examines the changes, contradictions and continuities in the magazine over time as it responded to political events, adapted to new commercial realities, and made use of technological advances. It explores how Billiken magazine not only reflected society, but shaped it through its influence on childhoods, children's culture and education, and provides an alternative window onto the history and politics of a tumultuous hundred years for Argentina.